L2 Willingness to Communicate of Indonesian High School Learners of English: An Exploratory Survey Study - Wendy Fernando; Adaninggar Septi Subekti (JPP (Jurnal Pendidikan dan Pembelajaran))
This study intends to explore Indonesian Senior High School learners’ second/foreign language (L2) Willingness to Communicate (WTC) in English. It employed a Google Form questionnaire as the method of collecting data. 159 L2 learners from more than six islands in Indonesia participated in this study. This study found that learners generally reported a moderate level of L2 WTC. They were moderately enthusiastic to speak in English class, moderately confident to use English in communication, and moderately willing to use English in small groups and pair work activities. However, seen from rather big standard deviations of the mean scores, the participants’ responses may be very heterogeneous, suggesting rather spread out values away from the mean scores. Pedagogical implications include promoting small-group activities and minimising whole-class discussions.